KOMPAK: The Program to Improve Quality of Life for Parents of Childhood Cancer Patients - Siti Nur Fauziyah Hukdar; Eva Meizara Puspita Dewi (ARRUS Journal of Social Sciences and Humanities, 2023)
Parents of Childhood Cancer patients as caregivers have an impact on the many tasks that must be undertaken and cause stress, causing physical and psychological burdens. As a caregiver, this is closely related to the increase in parenting stress which can lead to a decrease in the quality of life of the patient's parents. This study aims to determine the effectiveness of the intervention program "KOMPAK" to improve the quality of life of parents of children with cancer patients at YKAKI Makassar. This study uses the One Group Pre test & Post test Design research design. Participants in this study were parents of children with cancer who had a quality of life score of 69 < X 106 in the medium category and 69 < X 106 in the low category, as many as 6 people. The measuring instrument used is The CareGiver Oncology Quality of Life (CarGoQol). Data analysis technique used Wilcoxon signed-rank test. The results showed that there was a significant improvement in the quality of life of parents of children with cancer patients Z = -2.207, = 0.027 (Ï < 0.005. These results indicate that the "KOMPAK" program is effective in improving the quality of life of parents of childhood cancer patients at YKAKI Makassar. The findings in this study have implications for the implementation of activities to intervene to improve the quality of life and reduce the stress of parenting childhood cancer in parents of patients.